Fecal Calprotectin During Pregnancy in Women With Moderate-Severe Inflammatory Bowel Disease. Issue 4 (28th February 2018) - Kammerlander, Heidi; Nielsen, Jan; Kjeldsen, Jens; Knudsen, Torben; Gradel, Kim Oren; Friedman, Sonia; Nørgård, Bente Mertz
Abstract: Background: Fecal calprotectin (FC) is a biomarker used for assessing disease activity among IBD patients. Sparse knowledge exists as to whether FC correlates with clinical disease activity during pregnancy. Our aim was to assess FC and selected biomarkers in women with moderate-severe IBD and correlate them with clinical disease activity scores in pregnant women. Methods: We identified a nationwide cohort of 219 singleton pregnancies in women with moderate-severe disease (all treated with anti–tumor recrosis factor–α [anti-TNF-α] therapy during pregnancy), and we reviewed the medical records to extract clinical details and information on biomarkers. FC, C-reactive protein (CRP), hemoglobin, and albumin were collected according to each trimester. Results: A total of 346 FC measurements were obtained throughout the gestational periods. FC values were between 80–120, 259–349, and 778–1277 mg/kg in women with clinically inactive, mild, and moderate-severe disease activity, respectively, and were significantly higher among the women with clinical disease activity. ROC curves for disease activity were computed according to the preconception period: 0.81 (95% confidence interval [CI], 0.69–0.93), first trimester: 0.73 (95% CI, 0.60–0.86), second trimester: 0.74 (95% CI, 0.62–0.86), and third trimester: 0.76 (95% CI, 0.64–0.88), respectively. We found a sensitivity of 69.7%–80.0%, a specificity of 66.7%–73.3%, and a positive predictive value of 66.7%–74.4% over the 4 gestational periods when a cutoff of 200 mg/kg was used. We found no clinically significant differences in CRP, albumin, or hemoglobin. Conclusions: FC in pregnant women with moderate-severe IBD treated with anti-TNF-α therapy was significantly higher in women with clinical disease activity compared with the women without. FC correlated with the level of clinical disease activity in all gestational periods.